Inhibition of p38 MAPK attenuates renal atrophy and fibrosis in a murine renal artery stenosis model - Wang, Diping (American Physiological Society, 2013)
Renal artery stenosis (RAS) is an important cause of chronic renal dysfunction. Recent studies have underscored a critical role for CCL2 (MCP-1)-mediated inflammation in the progression of chronic renal damage in RAS and other chronic renal diseases. In vitro studies have implicated p38 MAPK as a critical intermediate for the production of CCL2. However, a potential role of p38 signaling in the development and progression of chronic renal disease in RAS has not been previously defined. We sought to test the hypothesis that inhibition of p38 MAPK ameliorates chronic renal injury in mice with RAS. We established a murine RAS model by placing a cuff on the right renal artery and treated mice with the p38 inhibitor SB203580 or vehicle for 2 wk. In mice treated with vehicle, the cuffed kidney developed interstitial fibrosis, tubular atrophy, and interstitial inflammation. In mice treated with SB203580, the RAS-induced renal atrophy was reduced (70% vs. 39%, P < 0.05). SB203580 also reduced interstitial inflammation and extracellular matrix deposition but had no effect on the development of hypertension. SB203580 partially blocked the induction of CCL2, CCL7 (MCP-3), CC chemokine receptor 2 (CCR2), and collagen 4 mRNA expression in the cuffed kidneys. In vitro, blockade of p38 hindered both TNF-α and TGF-β-induced CCL2 upregulation. Based on these observations, we conclude that p38 MAPK plays a critical role in the induction of CCL2/CCL7/CCR2 system and the development of interstitial inflammation in RAS.